PERANAN KEPOLISIAN DALAM UPAYA PENCEGAHAN TINDAK PIDANA PERJUDIAN DING DONG/SLOT MACHINE DI WILAYAH HUKUM KEPOLISIAN SEKTOR MANDAU - Ranto Kaya, Dela Ware; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Gambling is one of the social ills that need to be prevented and eradicated due to the impact of the implementation is a disturbance to social order especially specialized in gambling Dingdong / Slot machine. As state officials who run the law enforcement function, the maintenance of public order and safety and protection, shelter and community services, police on duty to prevent and combat the crime of gambling Dingdong / Slot machine are.The purpose og this thesis, namely: What is the role of the Police Sector Mandau in preventing Crime Gambling Ding Dong / Slot Machine in Jurisdiction police forces Sector Mandau, what are the constraints faced by the Police Sector Mandau in preventing Gambling Ding Dong / Slot Machine, to know the efforts made by the Police Sector Mandau to overcome the obstacles in the prevention of the crime of gambling Dingdong / Slot machine in District Mandau. With the effort required to overcome the obstacles preventing and combating the crime of gambling arcade / slot machine should be further improved by conducting periodic repairKeywords : Role â Police Sector Mandau - Prevention of Gambling âDingDong/Slot machine